Kwantitatiewe spektro-chemiese bepaling van arseen in organiese materiaal - Steyn, A. P.(Andries Pieter) (Stellenbosch : Stellenbosch University, 2012)
Tesis (M. Sc.) -- Universiteit van Stellenbosch, 1945.